The Influence of Capital, Independence, and Education on Women's Entrepreneurial Motivation in Indonesia - Agustin Basriani; Desi Susanti; Rahmi Zainal; Deviana Sofyan (Husnayain Business Review, 2021)
This study aims to determine the motivation of women in entrepreneurship, especially in the culinary field in Pekanbaru, by using the variables of capital, independence, and education to analyze their influence on entrepreneurial motivation. The population in this study are all women who carry out home-based businesses engaged in home-based culinary businesses in Pekanbaru City whose numbers are not known with certainty, for an unknown population the number of samples in this study using the Wibisono formula and obtained a total sample of 97 people. Data was collected using the questionnaire method, namely by providing a list of statements directly to the respondents. The data analysis technique used is multiple linear regression analysis which is operated through the SPSS 20 for Windows program. The results of the study indicate that either simultaneously or partially, the variables of capital, independence, and education have a significant effect on the motivation of women who are culinary entrepreneurs in Pekanbaru.